Impact of HPMC on inhibiting crystallization and improving permeability of curcumin amorphous solid dispersions. (1st February 2018) - Fan, Na; He, Zhonggui; Ma, Pingping; Wang, Xin; Li, Chang; Sun, Jin; Sun, Yinghua; Li, Jing
Graphical abstract: Highlights: HPMC inhibited Cur crystallization by forming hydrogen bond with drug in ASDs. HPMC improved membrane permeability by lowering order level of phospholipid bilayer. Cur-E100/HPMC 6:1 was superior in improving dissolution and permeability of Cur. Abstract: The purpose of this paper was to elucidate the impacts of hydroxypropylmethyl cellulose E5 as assistant excipient on inhibiting crystallization and improving membrane permeability in curcumin amorphous solid dispersions that formulated by Eudragit E100. Intermolecular interactions formed between curcumin and polymers were probed using in situ Raman imaging and infrared spectroscopy. The abilities of hydroxypropylmethyl cellulose E5 in inhibiting crystallization and improving membrane permeability were confirmed by fluorescence spectroscopy, dynamic light scattering analysis and in vitro permeability experiment. The results demonstrated hydroxypropylmethyl cellulose E5 was significant in maintaining the amorphous drug concentration owing to the hydrogen bond interactions formed with curcumin, rending its ability to inhibit crystallization by reducing drug droplet size. Furthermore, the addition of hydroxypropylmethyl cellulose E5 in curcumin amorphous solid dispersions promoted drug membrane permeability through lowering the order level of phospholipid bilayer layer.